Analisis Dampak Intensitas Cahaya Reklame Terhadap Tingkat Pelayanan Jalan bagi Pengguna Jalan - A. R. Indra Tjahjani (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2022)
The lively installation of billboards in big cities adds to the beauty of the town. DKI Jakarta has made improvements along Jalan M.H. Thamrin arrived at Jl. Fatmawati. The purpose of the study was to find out the opinion of people who crossed the study area in the comfort of driving at night. The purpose of installing billboards is as a promotion media, as well as information media from various agencies. The method used is the theory of road performance and community responses collected using a questionnaire via google form to the community selected based on the purposive sampling method, obtained 47 respondents in the age range of 22-58 years. The level of service that shows road performance is at the level of service (LOS) A where the value of DS = 0.1 and the average speed on Fatmawati road for the Lebak Bulus direction is 20 km/hour with LOS B, while the Blok M direction is 26 km/hour with LOS B. Likewise the speed on the road M.H. Thamrin the direction of Jl. Jend Sudirman is 5 km/hour with LOS D, and the direction of Jl. Jend. Sudirman is towards Jl. Thamrin 40 km/hour. Respondents consisting 87.2% of these men stated that the existence of billboards in various forms needed to be maintained (53.2%). With LOS C, it is recommended that the installed billboards be reduced in lighting so as not to interfere with the focus of road users who are passing. However, respondents also said that the installation of billboards in the form of billboards with lighting was widely used in Europe and America.